2020
DOI: 10.1101/2020.02.27.968016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose-dependent phorbol 12-myristate-13-acetate-mediated monocyte-to-macrophage differentiation induces unique proteomic signatures in THP-1 cells

Abstract: 1, 2). Monocytes in the blood circulation migrate to the site of infection/inflammation and 48 differentiate into macrophages for effective host defense, tissue remodeling, and repair (3). 49Furthermore, macrophages exhibit a high level of plasticity, depending on their local 50 microenvironment, specialized functions and varied phenotype acquired (1, 4). 51Several models are employed to study the mechanisms of immune-modulation in monocytes 52 and macrophages during inflammatory diseases. The most frequently … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…After differentiation, the THP-1 cells became adherent with a lower proliferation rate. In agreement with the literature [ 41 , 42 ], the increase in the CD14 marker on the cell surface was another sign of completed differentiation ( Figure S1 in the Supplementary Materials ).…”
Section: Discussionsupporting
confidence: 91%
“…After differentiation, the THP-1 cells became adherent with a lower proliferation rate. In agreement with the literature [ 41 , 42 ], the increase in the CD14 marker on the cell surface was another sign of completed differentiation ( Figure S1 in the Supplementary Materials ).…”
Section: Discussionsupporting
confidence: 91%
“…Data storage and handling are supported under the NIRD/Notur project NN9036K. This manuscript has been released as a pre-print at bioRxiv ( 61 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…It has been shown that GM-CSF and M-CSF, two commonly used factors in the experimental differentiation of macrophages from monocytes, can differentially regulate M1-M2 marker expression at baseline and also predispose macrophages to enhanced M1 and M2 responses, respectively, when further challenged by other stimuli ( Hamilton et al., 2014 ; Fleetwood et al., 2007 ). Different concentrations and durations of PMA (phorbol 12-myristate-13-acetate), which is widely used to condition the human monocytic THP-1 cells, also results in wide variations of downstream protein expression and ultimately nontrivial differences in their polarization responses ( Pinto et al., 2020 ). In addition, innate genetic differences between human and mouse macrophage cell lines ( Thomas and Mattila, 2014 ), between cell lines of human origin ( Mendoza-Coronel and Castanon-Arreola, 2016 ; Shiratori et al., 2017 ), and between mouse cell lines derived from different strains ( Santos et al., 2006 ) can all lead to differential macrophage phenotype outcomes (e.g., inconsistent marker expression patterns) when these cells are treated with the same stimulation.…”
Section: Discussionmentioning
confidence: 99%